ANALISIS PENERAPAN PROMOTION MIX DALAM MENINGKATKAN JUMLAH NASABAH PADA PD BPR BANK BAPAS 69 KANTOR CABANG MAGELANG UTARA - Astutik, Liya Rizki Dewi; Achsa, Andhatu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2020)
Badan Perkredian Rakyat (BPR) which was named the best BUMD 2020 in the award of 2nd Infobank. The purpose of the research carried out in the first trimester of 2020 is to find out how the role of the promotion mix is in increasing the number of customers at PD BPR Bank Bapas 69 North Magelang Branch Office in the first trimester of 2020. Data management and analysis techniques are carried out using descriptive analysis techniques by analyzing previously collected data then presents the data that has been processed in the form of a description that explains the object under study. Data obtained by observing related companies and secondary data in the form of annual reports of branch offices annual reports which are then processed and analyzed based on existing theories. In order to increase the number of customers, PD. BPR Bank Bapas 69 use promotion mix variable such as advertising, personal selling, sales promotion, public relations and publicity, and direct marketing. The results from the research we can see that the promotion mix applied has an effect on increasing the number of customers at PD BPR Bank Bapas 69 North Magelang Branch Office seen from the 2020 branch office annual report.